Game design documents for mobile elementary school mathematic educative games - jordy, Roy Jordy; Marcos, Hendra; Wijaya Kusuma, Jaka; Intan Surya Saputra, Dhanar; Purwadi, Purwadi (SHM Publisher, 2023)
Mobile games or games in this era are very much in demand by young people and small children as a medium of entertainment. Even the elderly are still often encountered playing this mobile game. This has prompted many game developer programmers to want to make mobile-based games. This aims to add insight, especially at the age of children, so that they are more enthusiastic about learning through this educational game. The academic side of this game comes from simple and fun math puzzles. From within this game, players can enjoy games that have 2D animations and are based on Android, as well as enriching children's knowledge and learning basic mathematical calculations by answering using games or this educational game. The assessment of this educational game is assessed when based on the number of correct answers. The method used in this research is in the form of collecting information and data, which includes recording and studying the literature and will conduct searches using the internet, as well as data sources relating to the problems in this research game Development. Lifecycle (GDLC) is used as a system development method. GDLC is a guide or guidelines that can regulate the rules in making this educational game. The results of this research will be the realization of mobile or android-based games with construct 2 for elementary school children from grades 3, 4, and 5. This android-based educational game is expected to provide experience to children in the world of learning and can increase elementary school children's interest in arithmetic, especially in counting.